An Improvement Of Medan City Merdeka Field Design Based On Community Participation Approach - Benny Iskandar (INFOKUM, 2022)
Medan Merdeka Square is one of the public green open spaces located right in the heart of Medan, which should be able to become a water absorption area and an absorber for air pollution in the city of Medan. And it should also be able to meet the needs of public space activities for the people of the city of Medan, but in fact, it has not run optimally as the function of green open space. Through the Community Participation research process, this Merdeka Square redesign provides design results that are by the wishes of the community and meet the needs of activities as green open spaces function. So that there is no decrease in the quality and quantity of the environment in urban areas due to the non-optimal utilization of green open space as water catchment areas, restoring the balance between green open spaces and built-up spaces (non-green spaces), so that urban areas can be achieved with healthy and comfortable environmental conditions for their users.